The Density of Dermatophagoides sp. in Households and its Correlation with the Score for Allergic Rhinitis in Jember, East Java - Sulistyaningsih, Erma; Laili, Elisa Fadia; Abrori, Cholis (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2021)
The prevalence of allergic rhinitis (AR) in Indonesia is an estimated 24.3% and increasing each year. The majority cause of AR is house dust mites (HDMs) allergens, especially Dermatophagoides sp. The screening tool to estimate the prevalence and diagnose AF in a population setting is the Score for Allergic Rhinitis (SFAR) questionnaire. This study aimed to investigate the correlation between the density of Dermatophagoides sp. in households and the SFAR in Jember, East Java. The study enrolled 30 housewives as respondents, which were selected by stratified random sampling. Respondents were interviewed using the SFAR questionnaire. The dust sample from each house of the respondent was collected, the HDMs either Dermatophagoides sp. or others were identified and the density of Dermatophagoides sp. was calculated. Data were analyzed using the Pearson Test. Dermatophagoides sp. were found in 21 out of 30 samples and 11 out of 30 respondents had an SFAR of â‰¥ 7. The Pearson analysis showed the value of p = 0.555 and r = 0.136. Dermatophagoides sp. was the majority of species of HDMs, but there was no significant correlation between the density of Dermatophagoides sp. in households and the SFAR among housewivesÂ  in Jember.